Effect of Rifampin‐Mediated OATP1B1 and OATP1B3 Transporter Inhibition on the Pharmacokinetics of the P2Y12 Receptor Antagonist Selatogrel - Uta Schilling; Jasper Dingemanse; Christine Voors‐Pette; Christel Romeijn; Peter Dogterom; Mike Ufer (Wiley, 2020)
In vitro studies have indicated that the P2Y12 receptor antagonist selatogrel is a substrate of organic anion‐transporting‐polypeptide (OATP)1B1 and OATP1B3 that are known to mediate hepatic uptake. Selatogrel is primarily eliminated via the biliary route. Therefore, the study aim was to investigate the effect of rifampin‐mediated OATP1B1 and OATP1B3 inhibition on the pharmacokinetics (PK) of selatogrel. This was a randomized, double‐blind, placebo‐controlled, two‐period, crossover study in 14 healthy subjects. In each period, a single subcutaneous dose of 4 mg selatogrel was administered, either immediately after a single intravenous 30 minutes infusion of 600 mg rifampin or after placebo. Plasma samples were collected for 36 hours and analyzed using a validated liquid chromatography‐tandem mass spectrometry method. PK parameters of selatogrel were calculated using noncompartmental analysis. The effect of rifampin was explored based on geometric mean peak plasma concentration (Cmax) and area under the concentration curve from zero to infinity (AUC0-∞) ratios and for time of maximum plasma concentration (Tmax) by Wilcoxon signed rank test. In addition, the safety and tolerability of the study treatments were evaluated. The geometric mean ratios of Cmax and AUC0-∞ were 1.19 (90% confidence interval (CI) 1.11-1.28) and 1.43 (90% CI 1.36-1.51), respectively, indicating a minor selatogrel exposure increase when administered after an infusion of rifampin compared with placebo. Rifampin administration did not affect terminal half‐life (t½) or Tmax of selatogrel. All study treatments were safe and well‐tolerated. A single dose of 600 mg rifampin, a potent OATP1B1/1B3 inhibitor, did not impact the PK of selatogrel to a clinically relevant extent suggesting that OATP1B1 and OATP1B3 transporters do not play a major role in the elimination of selatogrel.